Pengembangan Media Pembelajaran Bahasa Arab Berbasis Portable Engklek Arabic Di Kelas IV Madrasah Ibtidaiyah - Teatantia; Nurhadi (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2020)
Learning Arabic at MI Sultan Agung holds on to translations and is mostly done by conventional methods. Students who are too active are considered to disturb the course of the lesson. Teachers cannot focus on developing competencies because they are burdened with other tasks and responsibilities. This study aims to develop the portable hopscotch media in learning Arabic, find out the feasibility of the media, and determine students' responses to the media. This study uses the type of research and development of the Borg and Gall model. The feasibility of the product was reviewed by one media expert lecturer, one material expert lecturer, one teacher as reviewer and responded by as many as 28 grade 4 MI Sultan Agung Yogyakarta students. The instrument used in this study was a questionnaire to see the product quality and student questionnaire responses to the media product. The results of expert assessment and student responses in the form of quantitative data were analyzed with assessment criteria and percentage of ideals. The result of this research and development is in the form of Arabic portable hopscotch media product. Based on the assessment of media experts, material experts and reviewers. Arabic portable hopscotch successively got a percentage of ideals of 85.8% (Very Good), 82.5% (Good) and 74.1% (Good). The response of 28 students in the trial of using Arabic portable hopscotch was Very Good, evidenced by the resulting data of 88.8%. From these results it can be concluded that the Arabic portable hopscotch media is suitable for use as a medium for learning Arabic.Keywords: Arabic portable hopscotch Media, Arabic Learning, Madrasah Ibtidaiyah.